Sexual Abuse in Adolescents Is Associated With Atypically Increased Responsiveness Within Regions Implicated in Self-Referential and Emotional Processing to Approaching Animate Threats - Blair, Karina S.; Bashford-Largo, Johannah; Shah, Niraj; Lukoff, Jennie; Elowsky, Jaimie; Vogel, Steven; Emmert, Amanda; Zhang, Ru; Dobbertin, Matthew; Pollak, Seth; Blair, James R. (Frontiers in Psychiatry, 2020)
Childhood sexual abuse is associated with significant subsequent pathology and neuro-developmental disruption. In particular, childhood sexual abuse has been associated with heightened threat sensitivity. However, little work has directly investigated this issue. In this study we examine the association of childhood sexual abuse to neural and behavioral responses to looming, threatening face stimuli. The study involved 23 adolescents with significant past sexual abuse and 24 comparison individuals matched on IQ, age and sex. Participants were scanned during a looming threat task that involved negative and neutral, human faces and animals that appeared to either loom towards or recede from the participant. We found that adolescents who had been previously subjected to sexual abuse, relative to comparison adolescents, showed increased neural responses to threatening looming stimuli in regions including rostral and superior frontal gyrus as well as posterior cingulate gyrus. In addition, they showed significantly increased facilitation of reaction times to looming stimuli, particularly if these were human faces. These data demonstrate that prior sexual abuse was associated with heightened neural responsiveness to looming threats in a series of regions beyond the amygdala. These data are interpreted within models of rostromedial frontal and posterior cingulate cortices that stress their role in self-referential emotional processing and emotional maintenance.